2010
DOI: 10.1002/jmr.1030
|View full text |Cite
|
Sign up to set email alerts
|

Force spectroscopy of barnase–barstar single molecule interaction

Abstract: Results of the single molecule force spectroscopy study of specific interactions between ribonuclease barnase and its inhibitor barstar are presented. Experimental data obtained for the force loading rate ranging 2-70 nN/s are well approximated by a single straight line, from which the dissociation barrier of the width of 0.12 nm and height of 0.75-0.85T10 S19 J can be inferred. The measured value of specific interaction does not depend on the NaCl concentration. This apparently contradicts the well-known depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…() and its newest version OpenFovea (Roduit et al ., ), as well as the Hooke software (Sandal et al ., ); see these original papers and that of Sekatskii et al . () for details of the data processing. Here, we would like only to underline that these software help to filter observed bond‐breaking events depending on their reliability (quality) and that the acting value of the force loading rate trueF˙ is calculated by analyzing the part of the force curve observed immediately prior to the bond rupture event.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…() and its newest version OpenFovea (Roduit et al ., ), as well as the Hooke software (Sandal et al ., ); see these original papers and that of Sekatskii et al . () for details of the data processing. Here, we would like only to underline that these software help to filter observed bond‐breaking events depending on their reliability (quality) and that the acting value of the force loading rate trueF˙ is calculated by analyzing the part of the force curve observed immediately prior to the bond rupture event.…”
Section: Methodsmentioning
confidence: 99%
“…Essentially the same experimental setup and procedure of tip and sample functionalization, which have been used for the SMDFS earlier and described in detail in our papers (Chtcheglova et al ., ; Bogachek et al ., , ; Sekatskii et al ., ), were exploited for almost all protein pairs used in this study, which enables us to give here only a rather brief account. The data were obtained in Lausanne using the atomic force microscope (AFM) Nanoscope IV “Picoforce,” Bruker Corp., Madison, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the recognition events between ligand–receptor pairs have been investigated for understanding the physiological roles of these biological proteins at molecular level. These pairs include an anticancer peptide fragment of azurin (a bacterial protein that can be internalized in cancer cells and induce apoptosis) with p53, p53 with Mdm2, ribonuclease barnase with its inhibitor barstar, and actin filament and binding protein …”
Section: Experimental Research Progressmentioning
confidence: 99%
“…Moreover, the recognition events between ligand−receptor pairs have been investigated for understanding the physiological roles of these biological proteins at molecular level. These pairs include an anticancer peptide fragment of azurin (a bacterial protein that can be internalized in cancer cells and induce apoptosis) with p53, 28 p53 with Mdm2, 29 ribonuclease barnase with its inhibitor barstar, 30 and actin filament and binding protein. 31 Bonazza and co-workers also utilized AFM to investigate the complex formation between the von Willebrand factor (VWF) and factor VIII (FVIII), two essential hemostatic components of human blood.…”
Section: Experimental Research Progressmentioning
confidence: 99%
“…The application of ASBB for self assembly of more complex supramolecular structures with desired prop erties from a ready to use set of modules, which include, in addition to proteins, nanoparticles of dif ferent nature, required a fundamental study of this process. It was shown that the interaction force of the two proteins, barnase and barstar, is sufficient for the association and retention of both nano and micropar ticles in one integral superstructure [38].…”
Section: Universal Modular Platform For Construction Of Targeted Multmentioning
confidence: 99%